Assessing Successful Land Claims and the Efficacy of CoManagement in Protected Areas - ZIKHO QWATEKANA; NOZIPHO PRUDENCE MAZIBUKO (African Journal of Governance and Development, 2020)
The aim of this paper is to assess successful land claims as well as the efficacy of comanagement in striking a balance between community land rights with the goals of conservation for tourism. The study adopted a qualitative approach, using a case of a successful land claim in the Tala Private Game Reserve, KwaZulu-Natal Province. A purposive sample was selected from the claimant community and semi-structured interviews were used to collect data. The findings reflect that co-management may be a logical approach to involving local communities in the management of protected areas. However, as a model used to address land claims by reconciling the necessity of conservation for tourism purposes with land rights, its efficacy remains in doubt. This study thus concludes that unless there is a reassessment of the co-management model and the role of the government in providing post settlement support, the rights of successful claimants will not be realised. It is essential that the government recognizes that sufficient time, support, and resources are fundamental to the success of co-management projects.